The Influence of Financial Ratios on Tax Avoidance - Sembiring, Anggata Pradija; Hasibuan, Thezar Fiqih Hidayat; Siregar, Retnawaty (Accounting and Business Journal, 2024)
This study aims to determine the extent of the influence of Sales Growth, Return on Assets, and Capital Intensity on Tax Avoidance in plantation sector companies listed on the Indonesia Stock Exchange from 2019 to 2022. This type of research is causal effect with a quantitative approach, and the sample data in this study amounts to 64, which represents data from 16 financial reports over the 4-year research period. The type of data in this study is secondary data. The analysis method used in this study is multiple regression analysis. The research results show that Sales Growth has a partially positive and significant effect on Tax Avoidance, Return on Assets (ROA) has a partially positive and significant effect on Tax Avoidance, and Capital Intensity has a negative and significant effect on Tax Avoidance. The F-test results indicate a positive and significant influence.